A policy brief: improving access and utilization of adolescent sexual and reproductive health services in Southern Ethiopia - Negussie Boti Sidamo; Amene Abebe Kerbo; Kassa Daka Gidebo; Yohannes Dibaba Wado (Frontiers Media S.A., 2024)
BackgroundAdolescent sexual and reproductive health (ASRH) is fundamental to the overall wellbeing and development of young people. In Southern Ethiopia, adolescents face significant barriers to accessing and utilizing ASRH services: they include limited information, pervasive cultural stigma, and inadequate healthcare infrastructure. Addressing these barriers is critical to reducing unintended pregnancies, preventing sexually transmitted infections, and achieving national and international health objectives. Despite the existence of policies aimed at improving ASRH, these challenges persist, highlighting the urgent need for targeted policy reforms and effective implementation strategies to ensure a healthier future for adolescents in the region.Main findingsRecent research has identified substantial barriers to ASRH services in Southern Ethiopia. Key challenges include widespread gaps in knowledge, socio-cultural stigma, and strong influences from family and peers, compounded by limited service availability. The absence of adolescent-friendly care, coupled with insufficient outreach efforts, further restricts access. Healthcare providers also encounter significant obstacles, such as stigma, inadequate training, and a lack of institutional support, which undermine their ability to deliver effective services. Service utilization varies markedly based on geographic location, economic status, and educational attainment, with approximately half of adolescents lacking a comprehensive understanding of sexual and reproductive health and rights (SRHR). Moreover, persistent stigma, low levels of social support, and limited self-efficacy continue to hinder the uptake of these essential services.Policy implicationsTo improve ASRH services in Southern Ethiopia, a multi-faceted approach is imperative. Increasing public education through school programs and awareness campaigns can mitigate stigma and misinformation, fostering a more supportive environment. Initiatives such as providing transportation support and establishing mobile health clinics will significantly improve access for adolescents in underserved areas. Strengthening healthcare services by offering specialized training for providers and establishing adolescent-friendly clinics will elevate the quality of care. Engaging families, communities, and peer networks is essential for building a supportive framework that encourages adolescents to utilize SRH services. Finally, implementing skill-building and counseling programs will empower adolescents to make informed decisions regarding their sexual and reproductive health, ultimately contributing to improved health outcomes across the region.